Are vipers prototypic fear-evoking snakes? A cross-cultural comparison of Somalis and Czechs - Frynta, Daniel; Elmi, Hassan Sh Abdirahman; Janovcová, Markéta; Rudolfová, Veronika; Štolhoferová, Iveta; Rexová, Kateřina; Král, David; Sommer, David; Berti, Daniel Alex; Landová, Eva; Frýdlová, Petra (Frontiers in Psychology, 2023)
Snakes are known as highly fear-evoking animals, eliciting preferential attention and fast detection in humans. We examined the human fear response to snakes in the context of both current and evolutionary experiences, conducting our research in the cradle of humankind, the Horn of Africa. This region is characterized by the frequent occurrence of various snake species, including deadly venomous viperids (adders) and elapids (cobras and mambas). We conducted experiments in Somaliland and compared the results with data from Czech respondents to address the still unresolved questions: To which extent is human fear of snakes affected by evolutionary or current experience and local culture? Can people of both nationalities recognize venomous snakes as a category, or are they only afraid of certain species that are most dangerous in a given area? Are respondents of both nationalities equally afraid of deadly snakes from both families (Viperidae, Elapidae)? We employed a well-established picture-sorting approach, consisting of 48 snake species belonging to four distinct groups. Our results revealed significant agreement among Somali as well as Czech respondents. We found a highly significant effect of the stimulus on perceived fear in both populations. Vipers appeared to be the most salient stimuli in both populations, as they occupied the highest positions according to the reported level of subjectively perceived fear. The position of vipers strongly contrasts with the fear ranking of deadly venomous elapids, which were in lower positions. Fear scores of vipers were significantly higher in both populations, and their best predictor was the body width of the snake. The evolutionary, cultural, and cognitive aspects of this phenomenon are discussed.